Analysis of Educational Structure and Value in Panjalu Folklore Using Structural Approach and Relevance to Literary Learning in Junior High School - Sukriyadi, Ajis; Setiartin R, Titin (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to describe the Panjalu folklore in Ciamis Regency, (1) the structure of the folklore, (2) educational values, and (3) its relevance to literature learning in junior high school. The research data were obtained from interviews, recordings, and documentation. The research was conducted using the literature study method. Qualitative data analysis technique used in this research is structural analysis and interactive model analysis a descriptive method. Folklore studied from the history book of the Panjalu story in six versions of the work of Djaja Sukardja are folk tales of the story of Prabu Borosngora and the story of Maung Panjalu. Folklore is studied with a structural approach and studied educational values. The study of the two folk tales using a structural approach found intrinsic elements, including characters and characterizations, plot, setting, theme, and message. both folk tales contain educational values including moral, cultural, religious, historical, and heroic values. folklore in Panjalu is relevant to the literary learning in junior high school.